2019
DOI: 10.3390/nu11010083
|View full text |Cite
|
Sign up to set email alerts
|

Association between Eating Speed and Classical Cardiovascular Risk Factors: A Cross-Sectional Study

Abstract: Cardiovascular disease (CVD) is one of the main causes of morbidity and mortality around the world. Lifestyle is recognized as a key factor in the development of metabolic disorders and CVD. Recently, eating speed has been of particular interest since some studies have associated it with the development of obesity and other cardiometabolic disorders. We aimed to assess the association between eating speed and various cardiovascular risk factors. We conducted a cross-sectional analysis within the framework of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 39 publications
3
66
0
Order By: Relevance
“…Eating fast is known to be associated with overweight and obesity [9][10][11], insulin resistance [16], metabolic syndrome [10,17] and T2DM [16,18]. Eating fast is also reported to be associated with a risk factor for CVD [31], which is associated with NAFLD [4,32].…”
Section: Discussionmentioning
confidence: 99%
“…Eating fast is known to be associated with overweight and obesity [9][10][11], insulin resistance [16], metabolic syndrome [10,17] and T2DM [16,18]. Eating fast is also reported to be associated with a risk factor for CVD [31], which is associated with NAFLD [4,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, although AD has also been observed to have significant positive effects on health, there is no widely used questionnaire to assess compliance with its recommendations. The index created by our group, presented in this manuscript, includes all these recommendations, adapting the responses to a food frequency questionnaire widely used in other research [30,31]. The composition and validation of an AD adherence questionnaire using this index may be of interest in initiating a debate in which both dietary patterns (Mediterranean and Atlantic) can be compared in terms of predicting cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Slower eating speed and higher consumption of home-prepared meals have been found to be associated with a lower risk of weight gain and a higher-quality diet. For instance, previous studies have found that, among adults, eating more slowly inhibits the development of obesity (Hurst and Fukuda 2018 ), and eating slower is associated with a lower risk of elevated triglycerides (Paz-Graniel et al 2019 ). Hamermesh ( 2010 ) and Zeballos and Restrepo ( 2018 ) show that there is an inverse relationship between time spent eating and body mass index (BMI), which suggests that the amount of time people spend eating may play a role in obesity.…”
Section: Introductionmentioning
confidence: 99%